Treatment with Lobeglitazone Attenuates Hepatic Steatosis in Diet-Induced Obese Mice - Sorim Choung; Kyong Hye Joung; Bo Ram You; Sang Ki Park; Hyun Jin Kim; Bon Jeong Ku (PPAR Research)
Nonalcoholic fatty liver disease (NAFLD) is strongly associated with insulin resistance. The peroxisome proliferator-activated receptor (PPAR) activators, thiazolidinediones, (TZDs), are insulin sensitizers used as a treatment for NAFLD. However, TZDs are a controversial treatment for NAFLD because of conflicting results regarding hepatic steatosis and fibrosis. To evaluate a possible effective drug for treatment of NAFLD, we investigated the effects of a newly developed TZD, lobeglitazone, with an emphasis on hepatic lipid metabolism. Lobeglitazone treatment for 4 weeks in high fat diet- (HFD-) induced obese mice (HL group) improved insulin resistance and glucose intolerance compared to HFD-induced obese mice (HU group). The gene levels related to hepatic gluconeogenesis also decreased after treatment by lobeglitazone. The livers of mice in the HL group showed histologically reduced lipid accumulation, with lowered total plasma cholesterol and triglyceride levels. In addition, the HL group significantly decreased the hepatic expression of genes associated with lipid synthesis, cholesterol biosynthesis, and lipid droplet development and increased the hepatic expression of genes associated with fatty acid β-oxidation, thus suggesting that lobeglitazone decreased hepatic steatosis and reversed hepatic lipid dysregulation. Livers with steatohepatitis contained increased levels of PPARγ and phosphorylated PPARγ at serine 273, leading to downregulation of expression of genes associated with insulin sensitivity. Notably, the treatment of lobeglitazone increased the protein levels of PPARα and diminished levels of PPARγ phosphorylated at serine 273, which were increased by a HFD, suggesting that induction of PPARα and posttranslational modification of PPARγ in livers by lobeglitazone might be an underlying mechanism of the improvement seen in NAFLD. Taken together, our data showed that lobeglitazone might be an effective treatment for NAFLD.